Enrichment of population density of a bacterial consortium during bioremediation of a soil under successive contaminations with diesel oil (Acta Scientiarum. Biological Sciences, 2018)
The effect of successive soil contamination with diesel oil was evaluated on population dynamics of a bacterial consortium (Acinetobacter baumannii LBBMA 04, Pseudomonas aeruginosa LBBMA 58, Ochrobactrum anthropi LBBMA 88b, Acinetobacter baumannii LBBMAES11, and Bacillus subtilis LBBMA 155) and on biodegradation of petroleum hydrocarbons (n-C12-C22). After each contamination with diesel oil, soil samples were collected for assessment of bacterial population and sequence of petroleum hydrocarbons degradation. At 20 and 40 days, the highest percentage of degradation was observed for the higher carbon chain hydrocarbons (n-C21 and C22). After the third contamination, there was a considerable reduction of n-C21degradation and a high degradation of hydrocarbons n-C13-15, C17 and C19, which contrasts with the low values of degradation of these hydrocarbons in the two previous phases. The highest growth rate of all members of the consortium occurred from 0 to 20 days, but population increase continued up to the end of the experiment (except for B. subitillis strain, whose population stabilized after 20 days). Our results show that the recurrent contamination by hydrocarbons affected the population structure of bacterial consortium and increased the total population density of the bacterial consortium.